Integration of Digital Citizenship in Civics Learning to Enhance Students' Democratic Participation: A Narrative Literature Review - Abd. Rahman; Rafida Rasyid; Abdul Latief (Sustainable, 2026)
The rapid digitalization of society has transformed civic engagement, yet high internet access has not consistently translated into ethical online behavior or critical digital literacy among university students. This study examines how integrating digital citizenship into Civic Education can enhance students’ democratic participation. Employing a narrative literature review, this research synthesizes peer-reviewed journals, academic books, and policy documents published between 2020 and 2026. The analysis reveals that digital citizenship encompasses digital literacy, ethical awareness, security, and active participation, all of which align closely with the foundational objectives of Civic Education. Effective integration requires moving beyond traditional instruction toward interactive pedagogical models, including project-based digital campaigns, structured online deliberation, and critical media analysis. These strategies significantly improve students’ capacity to evaluate information, engage in respectful discourse, and participate constructively in democratic processes. The study concludes that systematically embedding digital citizenship into Civic Education is essential for cultivating critically engaged and ethically responsible digital citizens. Successful implementation demands institutional support, continuous educator training, and curriculum adaptation.